The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5603/cj.a2016.0047
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress in the development of in-stent restenosis revisited. A critical review of clinical data on shear stress after intracoronary stent implantation

Abstract: The average wall shear stress (WSS) (Cardiol J 2016; 23, 4: 365-373)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
0
10
1
1
Order By: Relevance
“…In line with previous literature data, we demonstrated that the curvature of the target coronary artery segment significantly decreased after stenting due to the straightening effect of the stent. In contrast to some previous studies [8, 10, 27], our results did not support the idea that the straightening effect of the stent always generates an increase of the angles at the edges of the stent. In particular, we observed an increase after stenting in cases of pre-stent edge bending angles < 7°.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with previous literature data, we demonstrated that the curvature of the target coronary artery segment significantly decreased after stenting due to the straightening effect of the stent. In contrast to some previous studies [8, 10, 27], our results did not support the idea that the straightening effect of the stent always generates an increase of the angles at the edges of the stent. In particular, we observed an increase after stenting in cases of pre-stent edge bending angles < 7°.…”
Section: Discussioncontrasting
confidence: 99%
“…The mechanism behind this phenomenon was proposed to be the change of the wall shear stress, as a contributor of intimal hyperplasia [57]. However, the question “whether the detected intimal hyperplasia is a part of the healing process after stent implantation or a predictor of later clinical restenosis” has not yet been answered [8].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, provisional T-stenting (PTS) is the best approach [2,3]. However, the optimal strategy for coronary bifurcations treatment remains a subject of debate, mainly when the side branch (SB) is large, not easily accessible or narrowed by a long lesion [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At a macro-level, animal studies have shown that tissue regrowth in stented arteries is prominent at sites of low and/or oscillatory WSS [ 9 11 ]. Although limited by the small number of analyzed cases, some patient studies have found a similar relationship between neointimal regrowth and altered WSS pattern [ 12 ]. These evidences explain the recent research interest on the accurate quantification of patient-specific stented artery hemodynamics as a means to predict stent failure induced by thrombosis or in-stent restenosis in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%